2017
DOI: 10.7150/jca.19750
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effect of Metformin on the Survival of Lung Cancer Patients with Diabetes: A Comprehensive Systematic Review and Meta-analysis of Retrospective Studies

Abstract: Preclinical investigations have revealed an anti-cancer effect of metformin. Several studies of metformin treatment have demonstrated the improved clinical outcomes of lung cancer patients with diabetes; however, the results have been inconsistent among studies. Our systematic review and meta-analysis aimed to summarize the up-to-date effects of metformin on diabetic lung cancer patients.A systematic search was performed for studies published. Then, these studies were evaluated for inclusion, and relevant data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 47 publications
(83 reference statements)
1
28
1
1
Order By: Relevance
“…Clinical survival reports are used to summarize the therapeutic effects of care from clinics or hospitals 7 . PBCR survival can reflect the overall situation of cancer diagnosis and treatment, and even the general situation of health care 4 - 6 ; while survival case series could reflect overall treatment effects in a particular medical department or the use of a certain treatments 7 , 8 . However, reports reflecting comprehensive treatment outcomes of a specific hospital are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical survival reports are used to summarize the therapeutic effects of care from clinics or hospitals 7 . PBCR survival can reflect the overall situation of cancer diagnosis and treatment, and even the general situation of health care 4 - 6 ; while survival case series could reflect overall treatment effects in a particular medical department or the use of a certain treatments 7 , 8 . However, reports reflecting comprehensive treatment outcomes of a specific hospital are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Based on three current meta-analyses (one based on systematic review), potential efficacy of Metformin to prolong overall survival (OS) could be found in SCLC consistently. The pooled hazard ratio (HR) was 0.52 (P<0.05) in the three studies (7)(8)(9). However, for NSCLC their outcomes were controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that inhibitors targeting mitochondrial oxidative phosphorylation such as biguanides induce death of RCC cells and may become therapeutic options to overcome the disastrous consequences of SOD2abundance in RCC cells [9]. Furthermore, the antitumor effect of biguanides like metformin in patients with diabetes has been demonstrated in several carcinomas [23][24][25][26][27]. In order to target tumor cell mitochondria, applying biguanides to replacement therapy or drug repositioning should be proposed for patients with SOD2-abundant RCC for maintenance phase treatments after primary surgery debulking numbers of RCC cells.…”
Section: Discussionmentioning
confidence: 99%